2021
DOI: 10.1111/crj.13362
|View full text |Cite
|
Sign up to set email alerts
|

The use of transbronchial cryobiopsy for diffuse parenchymal lung disease in critically ill patients with acute hypoxemic respiratory failure—A case series

Abstract: Objectives: Accurate diagnosis and management of undifferentiated diffuse parenchymal lung disease (DPLD) in critically ill patients is challenging. Transbronchial forceps biopsies have limited utility and surgical lung biopsies can be detrimental for critically ill patients. Transbronchial cryobiopsy (TBC) has shown increased diagnostic yield compared to conventional forceps biopsy in DPLD. However, TBC has not been studied in intensive care unit (ICU) patients. In this case series, we describe our experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…It is worth mentioning that although all patients in this study were initially thought to have non-infectious diseases, some patients were found to have viral pneumonia. Previous studies have found similar results, regardless of the method of biopsy [3,4,25,[27][28][29]. In addition, it is also notable that four patients in our study had TBLC indicating a fibrotic phase of DAD, including two patients with a combined proliferative phase of DAD, but none of these four patients survived.…”
Section: Discussionsupporting
confidence: 83%
“…It is worth mentioning that although all patients in this study were initially thought to have non-infectious diseases, some patients were found to have viral pneumonia. Previous studies have found similar results, regardless of the method of biopsy [3,4,25,[27][28][29]. In addition, it is also notable that four patients in our study had TBLC indicating a fibrotic phase of DAD, including two patients with a combined proliferative phase of DAD, but none of these four patients survived.…”
Section: Discussionsupporting
confidence: 83%
“…However, some authors reported the use of two bronchoscopes: one bronchoscope for the cryoprobe and one bronchoscope wedged at the bronchus to control bleeding [17][18][19]; no complications have been described and diagnostic yield was good. A cryoprobe (2.4, 1.9 or 1.7 mm in diameter) is introduced into the lung under fluoroscopic guidance through the working channel of a flexible bronchoscope.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, treatment adjustment rates in patients who underwent TBLC were also higher than in those who underwent TBLB. Matta et al performed TBLC for diffuse parenchymal lung disease at the bedside of patients with acute hypoxemic respiratory failure without fluoroscopic guidance at two tertiary hospitals [ 34 ]. After pathological diagnosis made by TBLC, 88% of patients had treatment adjustments.…”
Section: Discussionmentioning
confidence: 99%